2006
DOI: 10.1007/s10620-006-9110-8
|View full text |Cite
|
Sign up to set email alerts
|

From Trials to a Real Hospital Setting: Effectiveness of Pegylated Interferon-α-2b/Ribavirin Combination Therapy for Naïve Chronic Hepatitis C Patients

Abstract: Registration trials regarding pegylated interferon treatment of hepatitis C have created great expectations for improved results, but there is little information on actual outcomes in everyday hospital practice. We aimed to define the effectiveness of this treatment in a hospital setting. Seventy-four naïve patients with hepatitis C treated with 12 kD-pegylated-interferon-alpha-2-b/ribavirin (PEG-IFN) were retrospectively analyzed in comparison with 54 patients treated with IFN-alpha-2-b/ribavirin (STANDARD IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…1). These findings support the results of other worldwide studies, that combination antiviral therapy can be safely and successfully used in clinical practice outside the setting of strict clinical trials [10][11][12][13][14]. Pegylated interferon and ribavirin have been established as the gold standard therapy for patients with CHC based on data from randomized controlled trial (RCT) performed mostly in Caucasian populations [5][6][7].…”
Section: Discussionsupporting
confidence: 78%
“…1). These findings support the results of other worldwide studies, that combination antiviral therapy can be safely and successfully used in clinical practice outside the setting of strict clinical trials [10][11][12][13][14]. Pegylated interferon and ribavirin have been established as the gold standard therapy for patients with CHC based on data from randomized controlled trial (RCT) performed mostly in Caucasian populations [5][6][7].…”
Section: Discussionsupporting
confidence: 78%
“…However, these studies did not incorporate the uptake of treatment among all patients presenting to these setting. In addition, the treated patients had favorable features for achieving SVR (e.g., predominantly Caucasian with a high prevalence of HCV genotypes 2 or 3) [9][10][11][12][13]. On the other hand, studies of drug users and racial and ethnic minorities have shown substantially lower SVR rates in clinical practice settings [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Current therapy for HCV infection is the combination of Pegylated-interferon (PEG-IFN) with ribavirin [1], [2]. This regimen has only suboptimal clinical efficacy and is with side-effects [3], [4].…”
Section: Introductionmentioning
confidence: 99%